Prodromus of a fern flora for Bolivia. XX. Cyatheaceae - Lehnert, Marcus; Kessler, Michael (Phytotaxa, 2018)
We provide a synopsis to the family Cyatheaceae in Bolivia, comprising 3 genera and 40 species, one of which is endemic.